Differential Characteristics of Fisheries Extension Personnel in Relation to Their Evaluation ofTechnology Transfer - Balasubramaniam, S.; Perumal, G. (Fishery Technology, 2025)
This paper deals with the characteristics of fisheries personnel engaged in technologytransfer work. Fourteen characteristics of Fisheries extension personnel in the Fish Farmers Development Agencies and Non-FFDA()rganisutions were studied. The seven characteristics namely, mode of ecruitment, rural-urban background, size of family, family placement, education, inservice training undergone and introversion-extravcrsion personality were found to be important in differentiating the various evaluation categories of the Fisheries extension personnel.